Edukasi Penyuluhan Pencegahan Human Immunodeficiency Virus (HIV) Pada Remaja di Kampung Biak Wilayah Kerja Puskesmas Abepantai - Ruth Yogi; Muji Lestari; Sri Wahyuni (Rena Cipta Mandiri, 2026)
Low health literacy, stigma surrounding HIV/AIDS, and limited access to accurate information often lead adolescents to hold misconceptions regarding HIV transmission and prevention. The service area of ​​the Abepantai Community Health Center (Puskesmas), which includes Biak Village, has a significant adolescent population. As members of the productive age group, adolescents in Biak Village require comprehensive HIV education to understand transmission routes, risk factors, prevention strategies, and the importance of avoiding stigma against People Living with HIV (PLHIV), as well as to become aware of available health services. Evaluations using knowledge questionnaires showed an increase in knowledge scores following the educational sessions; for instance, the average pre-test score rose from 68.5 to 88.7 in the post-test, representing an average increase of 20.2 points. The most significant improvements were observed in the understanding of correct HIV transmission routes and prevention methods, as well as the realization that HIV is not transmitted through social contact such as handshaking, sharing food, or hugging. It is hoped that participants will apply the knowledge gained in their daily lives, avoid high-risk behaviors, and act as agents of change by sharing accurate information about HIV prevention with their peers.